Community-and proximate-level factors associated with perinatal mortality in Nigeria: evidence from a nationwide household survey - Osita K. Ezeh; Edward O. Uche-Nwachi; Uchechukwu D. Abada; Kingsley E. Agho (BMC Public Health, 2019)
Abstract Background The perinatal mortality rate (PMR) in Nigeria rose by approximately 5% from 39 to 41 deaths per 1000 total births between 2008 and 2013, indicating a reversal in earlier gains. This study sought to identify factors associated with increased PMR. Methods Nationally representative data including 31,121 pregnancies of 7 months or longer obtained from the 2013 Nigeria Demographic and Health Survey were used to investigate the community-, socio-economic-, proximate- and environmental-level factors related to perinatal mortality (PM). Generalized linear latent and mixed models with the logit link and binomial family that adjusted for clustering and sampling weights was employed for the analyses. Results Babies born to obese women (adjusted odds ratio [aOR] = 1.46, 95% confidence interval [CI]: 1.13–1.89) and babies whose mothers perceived their body size after birth to be smaller than the average size (aOR = 1.92, 95% CI: 1.61–2.30) showed greater odds of PM. Babies delivered through caesarean section were more likely to die (aOR = 2.85, 95% CI: 2.02–4.02) than those born through vaginal delivery. Other factors that significantly increased PM included age of the women (≥40 years), living in rural areas, gender (being male) and a fourth or higher birth order with a birth interval ≤ 2 years. Conclusions Newborn and maternal care interventions are needed, especially for rural communities, that aim at counselling women that are obese. Promoting well-timed caesarean delivery, Kangaroo mother care of small-for-gestational-age babies, child spacing, timely referral for ailing babies and adequate medical check-up for older pregnant women may substantially reduce PM in Nigeria.